Implementing and Evaluating Restorative Justice Projects in Prison. (February 2015) - Crocker, Diane
This article describes a restorative justice project run in three Canadian prisons. The project, Partners in Healing, aimed to promote restorative justice by running restorative justice committees inside and recruiting volunteers from the community to participate along with prisoners. The main goals of the project were to increase participants' awareness of restorative justice and help prisoners gain an understanding of the effects of their crime(s). An evaluation of the project solicited stories about the restorative justice committees and this article reports on some of the evaluation findings. The qualitative data offer insights into how to best design a restorative justice project in prisons. It also reveals dilemmas associated with evaluating such projects. The article concludes that projects need to be guided by a clear conceptualization of restorative justice.